PD-L1 immunohistochemistry in patients with non-small cell lung cancer - Jotatsu, Takanobu; Oda, Keishi; Yatera, Kazuhiro (Journal of Thoracic Disease, 2018)
Programmed death ligand 1 (PD-L1) is one of two ligands for programmed death 1 (PD-1) and can be expressed in lymphocytes (T and B cells) and antigen-presenting cells, such as dendritic cells, macrophages, tumor cells and tumor-infiltrating immune cells.